Bimetal waveguide structure for GaN-based terahertz quantum cascade laser and preparation method thereof
By adopting bimetallic waveguide structure and ridge waveguide structure in GaN-based terahertz quantum cascade laser, the challenges of waveguide design and preparation in the prior art are solved, and laser performance with low loss and high efficiency radiation is achieved.
Patent Information
- Application Number
- CN202510276911.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-06-10
AI Technical Summary
The prior art is difficult to achieve high-efficiency and low-loss GaN-based terahertz quantum cascade lasers, especially in the design and preparation of waveguide structures that operate at room temperature.
A bimetallic waveguide structure is adopted, including a metal In layer on the self-receiving substrate, an eutectic alloy AuIn layer and a lower electrode metal layer. Combined with the ridge waveguide structure, a waveguide structure with low loss and high light field limiting factor is formed through multi-layer structure design and process step optimization.
Low power loss and better heat dissipation performance are achieved, the threshold gain of the laser is reduced, and the radiation efficiency is increased, allowing the GaN-based terahertz quantum cascade laser to operate effectively at room temperature.
Smart Images

Figure CN120127502A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a dual-metal waveguide structure for a GaN-based terahertz quantum cascade laser and a preparation method thereof, belonging to the technical field of semiconductor devices. Background Art
[0002] Due to the lack of semiconductor materials with band gaps in the terahertz (THz) and mid-infrared bands in nature, miniaturized, portable, and high-power quantum cascade lasers (QCLs) are the best choice for THz light sources. Traditional GaAs-based THz-QCLs are limited by the inherent characteristics of the materials, confined to 0.8 - 5.4 THz, and the operating temperature has not yet broken through the low-temperature bottleneck (200 - 250K). Terahertz technology is a typical cross-cutting frontier field with important strategic significance and broad application prospects, such as imaging, remote sensing, radar, communication (satellite, aerospace, air-to-air), metrology, non-destructive testing, etc. It can be applied to various industries such as material characterization, environmental monitoring, petrochemical industry, aerospace, biomedicine, medical diagnosis, national defense, and national security. However, the THz light source technology has not yet met the requirements of practical applications, which is a bottleneck problem restricting the development of the entire field.
[0003] The total optical phonon energy of GaN-based terahertz QCLs is much larger than that of traditional GaAs materials, and the polariton bandgap is between 17 and 22 terahertz. Therefore, it is expected to realize QCLs emitting 5 - 12 terahertz. However, the structure of GaN-based terahertz quantum cascade lasers is still a very challenging task. In addition to the difficulties in designing the active region of the quantum cascade laser and material epitaxial growth, another important aspect of realizing the operation of room-temperature GaN-based terahertz quantum cascade lasers is the design and preparation of the waveguide. A waveguide structure with low loss and high optical field confinement factor is beneficial to reducing the threshold gain of the laser. For traditional terahertz quantum cascade lasers, there are mainly two types of waveguide structures, the dual-metal waveguide structure (metal / n+ / QCL / n+ / metal, with the highest optical field confinement factor and the smallest loss) and the single-metal waveguide structure (metal / n+ / QCL / n++ plasmon / insulating substrate, with the second-highest optical field confinement factor and the second-smallest loss). The dual-metal waveguide uses metals as the top and bottom cladding layers to confine the optical field within the active region layer, and the single-metal waveguide uses a metal as the top cladding layer and a heavily doped n++ layer at the bottom of the active region layer to confine the optical field. Summary of the Invention
[0004] The purpose of the present invention is to provide a dual-metal waveguide structure for a GaN-based terahertz quantum cascade laser.
[0005] The purpose of the present invention is achieved by the following technical solutions:
[0006] A dual-metal waveguide structure for a GaN-based terahertz quantum cascade laser, the structure comprising: a metal In layer, a eutectic alloy AuIn layer, and a lower electrode metal layer sequentially arranged upward from a receiving substrate, and a ridge waveguide structure is arranged on the lower electrode metal layer, and each ridge waveguide structure sequentially comprises a lower n-type heavily doped contact layer, a GaN / AlGaN multiple quantum well layer, an upper n-type heavily doped contact layer, and an upper electrode metal layer.
[0007] Preferably, the GaN / AlGaN multiple quantum well layer comprises a plurality of periodic structures, and the periodic structure is an active region structure of a GaN terahertz laser with 2-well resonant phonons and phonon scattering injection, or an active region structure of a GaN terahertz laser with 3-well resonant phonons, and other active region structures of GaN terahertz quantum cascade lasers.
[0008] Preferably, the thickness of the lower n-type heavily doped contact layer and the upper n-type heavily doped contact layer is 10-100 nm; for GaN terahertz QCL lasers with a working frequency less than 7 terahertz, the doping concentration
[0009] 5x10 18 ~5x10 19 / cm 3 ; for lasers working in the frequency range of 7-12 terahertz, the doping concentration is 5x10 17 ~5x10 18 / cm 3 .
[0010] Preferably, the lower electrode metal layer and the upper electrode metal layer are a Ti / Al / Ni / Au structure with a thickness of 10-50 / 100-150 / 30-80 / 100-200 nm.
[0011] Preferably, the thickness of the metal In layer is 500-1500 nm, and the thickness of the eutectic alloy AuIn layer is 100-300 nm. The In layer serves as a solder during bonding, can form an alloy layer with Au, and the formed AuIn has good mechanical strength and can conduct electricity.
[0012] The present invention also discloses a preparation method for the above-mentioned dual-metal waveguide structure for a GaN-based terahertz quantum cascade laser, characterized in that the steps thereof include:
[0013] S1. Grow an AlGaN layer with an Al component of 0%-15% on a Si substrate, and then sequentially grow a lower n-type heavily doped contact layer, a GaN / AlGaN multiple quantum well layer, and an upper n-type heavily doped contact layer on the AlGaN layer;
[0014] S2. Deposit metal Ti / Al / Ni / Au on the surface of the Si substrate quantum cascade structure sample by electron beam evaporation, magnetron sputtering or thermal evaporation to form the lower electrode metal layer for ohmic contact, and obtain the device substrate;
[0015] S3. Anneal the Si substrate sample under nitrogen atmosphere;
[0016] S4. Evaporate gold on the receiving substrate, and then evaporate metal In to form the receiving support substrate;
[0017] S5. Flip-chip bonding: Align the metal Au layer of the device substrate and the metal In layer of the receiving support substrate face to face, and heat and press the two substrates simultaneously to make Au react with In to form the eutectic alloy AuIn, so that the two substrates are firmly bonded together;
[0018] S6. Pretreat the Si substrate on the back of the device substrate and thin its thickness to 100 - 150 μm;
[0019] S7. Use the two-step lost-wax method for wet etching to remove the Si substrate of the substrate. Before wet etching, use paraffin wax corroded by an anti-corrosion solvent to protect the surrounding and back of the chip, only expose the Si substrate, first use the corrosion solvent to corrode. When the Si near the paraffin wax is corroded partially and the AlGaN layer is exposed, stop the corrosion, and heat the paraffin wax again to make it tightly cover the buffer layer, then use the corrosion solvent again for corrosion until the Si substrate is completely removed;
[0020] S8. Remove the paraffin wax;
[0021] S9. Use dry etching ICP to completely remove the AlGaN layer on the top of the bonded chip;
[0022] S10. Lithographically form multiple upper electrode windows with a width of 50 - 300 μm and a length of 500 - 1500 μm on the top surface of the chip;
[0023] S11. Deposit metal Ti / Al / Ni / Au on the surface of the lithographed chip by electron beam evaporation, magnetron sputtering or thermal evaporation, strip the photoresist, and form the upper electrode metal layer for ohmic contact on the upper electrode window.
[0024] S12. Use the upper electrode metal layer obtained in the previous step as a self-aligned mask, and stop when using dry ICP etching the chip surface to the lower electrode metal layer, to form multiple ridge waveguide structures;
[0025] S13. Cleave and package the chip.
[0026] Preferably, the ratio of the corrosion solvent used in the wet etching is concentrated nitric acid: hydrofluoric acid: glacial acetic acid = 4.5 - 5.5: 4.5 - 5.5: 1.5 - 2.5.
[0027] Preferably, the thickness of the metal In layer evaporated on the receiving substrate in step S4 is 1400 - 1500 nm.
[0028] The dual - metal waveguide structure in the present invention has low loss and high optical - field confinement factor, low power loss and better heat - dissipation performance, which is beneficial to reducing the threshold gain of the laser and increasing the radiation efficiency. Description of the Drawings
[0029] Figure 1 It is a schematic cross - sectional view of the dual - metal waveguide structure of the GaN - based terahertz quantum cascade laser.
[0030] Figure 2 It is a schematic structural view of growing qcl by molecular beam epitaxy on the Si substrate in step S1.
[0031] Figure 3 It is a schematic view of evaporating the Ti / Al / Ni / Au layer and the In layer in steps S2 and S4.
[0032] Figure 4 It is a schematic view of flip - chip bonding in step S5.
[0033] Figure 5 It is a schematic view of wet etching by the two - time lost - wax method in step S7.
[0034] Figure 6 It is a schematic view of the device after removing paraffin in step S8.
[0035] Figure 7 It is a schematic view of the device after photolithography in step S10.
[0036] Figure 8 It is a schematic view of the device after depositing metal and stripping the photoresist in step S11.
[0037] Figure 9 It is a schematic view of the overall process flow.
[0038] Figure 10 It is a three - dimensional schematic view of the dual - metal waveguide structure of the GaN - based terahertz quantum cascade laser.
[0039] Description of Component Labels:
[0040] A1 GaAs substrate
[0041] A2 Metal In layer
[0042] A3 Eutectic alloy AuIn layer
[0043] A4 Lower - electrode metal Ti / Al / Ni / Au layer
[0044] A5 Lower n - type heavily doped contact layer
[0045] A6 multi - quantum well layer
[0046] A7 upper n - type heavily doped contact layer
[0047] A8 upper electrode metal Ti / Al / Ni / Au layer
[0048] A9 AlGaN protective layer
[0049] A10 Si substrate
[0050] A11 paraffin wax
[0051] A12 photoresist Specific implementation manners
[0052] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in combination with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.
[0053] Embodiment 1
[0054] This gallium nitride terahertz quantum cascade laser with a bimetallic waveguide structure has a structure as Figure 1 and Figure 10 shown. Starting from the receiving substrate A1 upwards in sequence are a metal In layer A2, a eutectic alloy AuIn layer A3, and a lower electrode metal Ti / Al / Ni / Au layer A4. On the lower electrode metal Ti / Al / Ni / Au layer A4, a plurality of ridge waveguide structures are provided. Each ridge waveguide structure sequentially includes a lower n - type heavily doped contact layer A5, a GaN / AlGaN multi - quantum well layer A6, an upper n - type heavily doped contact layer A7, and an upper electrode metal Ti / Al / Ni / Au layer A8. Figure 1 and Figure 10 As a schematic diagram, 2 bimetallic waveguide structures are shown. In the actual device fabrication, usually dozens to hundreds of devices can be fabricated on one epitaxial wafer (determined according to the chip area, usually recommended to be 20 - 150), and then cleavage is performed. Each device contains a bimetallic waveguide structure.
[0055] The cavity length of the laser is 300 - 1500 um (not shown in the figure).
[0056] Among them, both the upper and lower electrode metal layers are Ti / Al / Ni / Au with a thickness of (30 / 150 / 50 / 150 nm).
[0057] The GaN / AlGaN multi-quantum well layer includes multiple periodic structures. The periodic structure is the active region structure of a GaN terahertz laser with 2-well resonant phonons and phonon scattering injection, or the active region structure of a GaN terahertz laser with 3-well resonant phonons, as well as other active region structures of GaN terahertz quantum cascade lasers.
[0058] In addition to forming a good ohmic contact with the metal layer, the upper and lower n-type heavily doped layers also have a greater impact on the loss due to their electron concentration and contact layer thickness. We studied n-type heavily doped contact layers with thicknesses ranging from 5 to 50 nm to investigate the effect of contact layer thickness on the loss. To achieve lasing in the range of 6 - 8 terahertz while reducing the gain loss, a 10-nm n+ contact layer thickness is the optimal choice. With other parameters fixed, the electron density of the n-type heavily doped layer is between 5*10 17 ~1*10 19 / cm 3 ³.
[0059] The present invention uses a GaAs substrate as the receiving substrate because GaAs has a four-fold symmetric structure. When cleaving, the two directions of the square chip are cleavage planes. The GaN device on the GaAs receiving substrate will break along the cleavage direction of GaAs, which is beneficial for forming a laser cavity with better quality. In the present invention, GaN can also be used as the receiving substrate. GaN has a good thermal conductivity of 130 - 210 W / (m*K). In the present invention, SiC can also be used as the receiving substrate because its thermal conductivity is 120 - 490 W / (m*K), which has good thermal performance compared to other semiconductor materials and is beneficial for the laser to operate under high-temperature conditions.
[0060] Example 2
[0061] As Figure 9 shown, the preparation method of a bimetallic waveguide structure gallium nitride terahertz quantum cascade laser includes the following steps:
[0062] S1 Use molecular beam epitaxy to sequentially grow an AlGaN layer A9 with an Al composition of 0.3% - 10% on the Si substrate A10; then grow an upper n-type heavily doped contact layer A7, a multi-quantum well active region A6, and a lower n-type heavily doped contact layer A5 on the AlGaN layer, as Figure 2 shown; for the A9 layer on the Si substrate, the usual choice is to directly grow a GaN layer. However, as the lattice grows thicker, it is easy for the epitaxial structure to crack due to stress accumulation. In the present invention, choosing to grow an AlGaN layer with an Al composition of 0.3% - 10% can effectively match the average composition of the upper superlattice, thereby reducing stress, increasing the thickness that the upper AlGaN quantum well structure can grow, and preventing the upper growth structure from cracking;
[0063] In the preparation process of the bimetallic waveguide, an electron beam evaporation coating system (Electron Beam Evaporation, EBE) is used to deposit a metal immersion Ti / Al / Ni / Au (30 / 150 / 50 / 150 nm) on the surface of the Si substrate quantum cascade structure sample, and an ohmic contact lower electrode metal layer is formed on the surface of the lower n-type heavily doped contact layer A5;
[0064] Wait for the electron beam evaporation to end, and anneal the sample under nitrogen conditions;
[0065] Deposit In on the receiving substrate to form a eutectic alloy AuIn with the topmost metal Au of the device substrate. Use a vacuum coating machine to deposit 1400 - 1500 nm of metal In on the receiving support substrate for subsequent flip-chip bonding. Using Au-In bonding improves the mechanical strength of the waveguide and the thermal stability during high-temperature operation of the device.
[0066] After depositing the metal on the top, the flip-chip bonding process needs to be carried out immediately. Under high temperature and pressure, the Au-In reaction forms a eutectic alloy to firmly bond the two substrates together. The process is as Figure 4 shown.
[0067] Preprocess the Si substrate on the back of the device substrate, thin the thickness to 100 - 150 μm, and then perform wet etching. First, use a mechanical thinning machine to thin by 700 - 750 μm, and the final thinned Si thickness is 100 - 150 μm. The advantage of using both mechanical thinning and wet etching is that it can uniformly and quickly remove the Si substrate without damaging the active region structure; if only mechanical thinning is used, it is difficult to precisely control the thickness, either over-thinning and breaking the lower layer, or failing to completely remove the Si substrate; if only wet etching is used, there will be problems of slow etching rate and uneven etching.
[0068] S7 As Figure 5As shown, the Si substrate of the substrate is removed by wet etching using the lost wax method twice. Before wet etching, Apiezon wax, which is resistant to strong acid corrosion, is used to protect the surrounding and back of the chip, leaving only the Si substrate exposed. First, the corrosion solvent is used to corrode for 10 minutes. After the part of the Si near the wax is corroded first, we stop the corrosion at this time, and then heat the wax again to make it closely cover the buffer layer. Then, the mixed acid is used again for corrosion until the Si substrate is completely removed. If only single corrosion is carried out, due to the unevenness of wet etching, after the part of the Si near the wax is corroded first, a gap will be generated between the wax and the substrate, causing the mixed acid to corrode the underlying metal. The advantage of two - time corrosion is that this gap can be re - sealed and the underlying metal electrodes can be protected. In the method of wet etching Si, the most commonly used corrosion solvent is a mixture of nitric acid, hydrofluoric acid and water (or glacial acetic acid). In the corrosion solution, water is used as a diluent, but acetic acid (CH3COOH) is preferably used because acetic acid can inhibit the decomposition of nitric acid, thus maintaining the concentration of nitric acid at a relatively high level. Nitric acid oxidizes Si, and then HF acid is used to react with SiO2 to remove SiO2, so as to achieve the purpose of corroding Si. The ratio of the corrosion solution is very important. If the proportion of nitric acid is too small, it will take a very long time to corrode 100um of Si. If the proportion of nitric acid is too large, a large number of bubbles will be generated by the violent reaction, which will damage the substrate. We optimized the ratio and dilution degree of the solution through a series of experiments, and the corrosion solvent selected is concentrated nitric acid: hydrofluoric acid: glacial acetic acid = 4.5 - 5.5:4.5 - 5.5:1.5 - 2.5.
[0069] S8 After the wet etching is completed, D - limonene is used to remove the Apiezon wax, and the obtained device structure is as Figure 6 shown. The advantage of this solvent is that it is non - toxic and has high safety;
[0070] S9 Use dry etching icp to completely remove the AlGaN protective layer on the top of the bonded chip, use BCl 3 gas for etching, and the etching rate is 330nm / min;
[0071] S10 Use AZ5214 photoresist (negative photoresist) for photolithography to form the pattern of the ridge waveguide. Using the AZ5214 photoresist negative photoresist process, an upper electrode window of 150 - 250nm is formed, as Figure 7 shown.
[0072] S11 Use an electron beam metal evaporation coating system (Electron Beam Evaporation, EBE) to deposit metals of Ti / Al / Ni / Au (30 / 150 / 50 / 150nm) by metal immersion on the surface of the photolithographed chip, and then strip the photoresist to form the ohmic contact upper electrode metal layer, as Figure 8 shown.
[0073] S12 uses the ohmic contact upper electrode metal layer in the previous step as a self-aligned mask, and stops etching by dry ICP until reaching the lower electrode to form a ridge waveguide structure. BCl 3 gas etching is used, and the etching rate is 330 nm / min. If a photoresist mask is used, the photoresist will carbonize after ICP, and the conductivity of the ohmic contact will be affected when using ozone to remove the photoresist. The advantage of the metal self-aligned mask is to avoid the influence on the ohmic contact when removing the photoresist.
[0074] S13 cleaves and packages the chip.
[0075] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited by the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and are all included in the protection scope of the present invention.
Claims
1. A bimetallic waveguide structure for GaN-based terahertz quantum cascade lasers, characterized in that Its structure includes: a metal In layer, a eutectic alloy AuIn layer, and a lower electrode metal layer arranged in sequence from a receiving substrate upward, a ridge waveguide structure is arranged on the lower electrode metal layer, and each ridge waveguide structure includes a lower n-type heavily doped contact layer, a GaN / AlGaN multi-quantum well layer, an upper n-type heavily doped contact layer and an upper electrode metal layer in sequence.
2. The bimetallic waveguide junction for GaN-based terahertz quantum cascade laser according to claim 1 The structure is characterized by: The receiving substrate is made of GaAs, SiC and GaN.
3. The bimetallic waveguide structure for GaN-based terahertz quantum cascade laser according to claim 1, characterized in that: The GaN / AlGaN multi-quantum well layer includes 5-500 periodic structures, and the periodic structure is a GaN terahertz laser active region structure with 2-well resonant phonons and phonon scattering injection, or a GaN terahertz laser active region structure with 3-well resonant phonons, or other GaN terahertz quantum cascade laser active region structures.
4. The bimetallic waveguide structure for GaN-based terahertz quantum cascade laser according to claim 1 or 2, characterized in that: The thickness of the lower n-type heavily doped contact layer and the upper n-type heavily doped contact layer is 10 to 100 nm; For lasers with operating frequencies less than 7 terahertz, the doping concentration is 5*10 18 ~5*10 19 / cm 3 ; For lasers operating in the frequency range of 7-20 terahertz, the doping concentration is 5*10 17 ~5*10 18 / cm 3 .
5. The bimetallic waveguide structure for GaN-based terahertz quantum cascade laser according to claim 1 or 2, characterized in that: The lower electrode metal layer and the upper electrode metal layer are Ti / Al / Ni / Au structures with thicknesses of 10-50 / 100-150 / 30-80 / 100-200 nm.
6. The bimetallic waveguide structure for GaN-based terahertz quantum cascade laser according to claim 1 or 2, characterized in that: The thickness of the metal In layer is 500-1500 nm, and the thickness of the eutectic alloy AuIn layer after bonding is 700-1700 nm.
7. The bimetallic waveguide structure for GaN-based terahertz quantum cascade laser according to claim 1 or 2, characterized in that: The ridge waveguide structure has a width of 50-300um and a length of 500-1500um.
8. The method for preparing a bimetallic waveguide structure for a GaN-based terahertz quantum cascade laser according to any one of claims 1 to 7, characterized in that The steps include: S1. growing an AlGaN layer with an Al component of 0%-15% on a Si substrate, and then sequentially growing an upper n-type heavily doped contact layer, a GaN / AlGaN multi-quantum well layer, and a lower n-type heavily doped contact layer on the AlGaN layer; S2. Depositing metal Ti / Al / Ni / Au on the lower n-type heavily doped contact layer on the surface of the Si substrate quantum cascade structure sample by electron beam evaporation, magnetron sputtering or thermal evaporation to form an ohmic contact lower electrode metal layer to obtain a device substrate; S3, annealing the Si substrate sample under nitrogen conditions; S4, evaporating gold on the receiving substrate, and then evaporating metal In to form a receiving support substrate; S5, flip-chip bonding: align the metal Au layer of the device substrate and the metal In layer of the receiving support substrate and place them face to face, and heat and pressurize the two substrates at the same time, so that Au and In react to form a eutectic alloy AuIn, so that the two substrates are bonded together; S6, pre-treating the Si substrate on the back of the device substrate to reduce the thickness to 50-200 μm; S7, using two lost wax wet etchings to remove the Si substrate of the substrate, before wet etching, the chip sidewalls and back are covered with anti-corrosion paraffin wax to expose the Si substrate and protect the eutectic alloy layer, the etching is performed twice: after one etching, the central area of the chip is an island Si, and the rest of the area is the AlGaN layer exposed after removing the Si substrate, the etching is stopped, the chip is rinsed to remove the corrosive solvent and the chip is dried; Before the second etching, paraffin wax is used again to tightly cover the chip sidewalls and the AlGaN layer exposed by the first etching, and then a second wet etching is performed to completely remove the Si substrate; S8, remove paraffin; S9, using dry etching icp to completely remove the AlGaN layer on the top of the chip after bonding; S10, photolithography is performed on the top surface of the chip to form a plurality of upper electrode windows with a width of 50-300 um and a length of 500-1500 um; S11, depositing metal Ti / Al / Ni / Au on the surface of the chip after photolithography by electron beam evaporation, magnetron sputtering or thermal evaporation, and then stripping and removing the glue to form an upper electrode metal layer with ohmic contact on the upper electrode window; S12, using the upper electrode metal layer obtained in the previous step as a self-aligned mask, using dry ICP to etch the chip surface and stop when the lower electrode metal layer is reached, to form a plurality of ridge waveguide structures; S13, disassemble and package the chip.
9. The preparation method according to claim 8, characterized in that The volume ratio of the corrosion solvent used in the wet corrosion is concentrated nitric acid: hydrofluoric acid: glacial acetic acid = 4.5-5.5: 4.5-5.5: 1.5-2.
5.
10. The preparation method according to claim 8, characterized in that The thickness of the metal In layer evaporated on the receiving substrate in step S4 is 1000-1500 nm.